(untitled) (Semiárida, 2018)
The present work was aimed to examine knowledge, practices and significations kept by vegetable gardeners regarding plant communities, and particularly weeds as species growing spontaneously in cropping lands. This research was carried out in the “Zona Norte” and “Villa Germinal” neighborhoods of Santa Rosa city, La Pampa. The topic of study was approached under ethnobotany and agroecology criteria. Collection of data using ethnobotanical tools, allowed the identification of 57 weed species. After performing a survey in both neighborhoods, it was revealed that about half of gardeners eliminate weeds without making use of them. The other half did mention using weeds mainly as fertilizer for gardens, but also as food for own domestic animals. In this study, the grass Cynodon dactylon was the most frequently found weed in gardens, being commonly considered a pest for that reason. The results of this work provide basic information for future research lines focusing on agroecology, small-scale agriculture and urban farming, as well as extension works involving government agencies and non-governmental organizations. This kind of studies can be useful to identify people’s unsatisfied demands.